Perancangan Gerak Tokoh Kelinci Pada Saat Menunggu Dalam 3D Animasi Pendek "Yue Bing" - Raynaldo Oscar Tandiary; Christine Mersiana Lukmanto (ULTIMART Jurnal Komunikasi Visual, 2020)
The writing is grounded from the writer’s interest on character animation process in an animation production, which becoming more popular in Indonesia these days. This particular research is all about the process of designing a rabbit character’s motion while waiting in the 3D animation short “Yue Bing”, so the happiness and enthusiasm, also the sadness and desperation felt by the character can be delivered to the audiences. This is done through the use of body language theories, secondary action, and timing animation principles. Throughout the process, research is done by looking at still and moving images on body language, secondary action, and timing as references, that later is translated to the three-dimensional software.